Disturbances of water and electrolyte balance - Hund, Ernst; Böhrer, Hubert; Martin, Eike; Hanley, Daniel F. (Neurocritical care, 1994)
Total body water, which is distributed into the intracellular and extracellular compartments, makes up 50-60% of the body weight of the average adult patient. The intracellular compartment contains 60% of total body water, the extracellular compartment 40%. The extracellular compartment can be further subdivided into the intravascular and interstitial subcompartments, with the former containing approximately 3.5 l in the average adult patient (i.e., 4% of body weight). These fluid compartments are known to undergo dynamic changes depending on a multitude of factors such as solute or protein concentrations.
Elektronische Reproduktion der Druck-Ausgabe 6. Dezember 2012
Gesehen am 08.05.2024